STRATEGI KEUNGGULAN KOMPETITIF RUMAH SAKIT DALAM ERA JAMINAN KESEHATAN NASIONAL (JKN): TINJAUAN LITERATUR HOSPITAL COMPETITIVE ADVANTAGE STRATEGIES IN THE NATIONAL HEALTH INSURANCE (JKN) ERA: A LITERATURE REVIEW - Nindirah Septia; Stevani Dewi Setyako; Purwadhi Purwadhi; Yani Restiani Widjaja (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2026)
The implementation of National Health Insurance (JKN) through BPJS Kesehatan since 2014 has fundamentally transformed the healthcare financing landscape in Indonesia. The Indonesian Case Base Groups (INA-CBGs) payment system compels hospitals to adopt more efficient and competitive management strategies. This literature review aims to examine competitive advantage strategies employed by hospitals in response to JKN system pressures, including cost leadership strategies, service differentiation, clinical pathway optimization, Bed Occupancy Rate (BOR) and Length of Stay (LOS) management, and center of excellence development. Literature searches were conducted through PubMed, Google Scholar, and Garuda databases covering 2014-2024 using keywords related to JKN, BPJS, hospital management, and competitive strategy. Findings indicate that hospitals maintaining their competitiveness successfully combine cost efficiency strategies with high-quality service differentiation. Clinical pathway optimization has proven capable of reducing average treatment costs by 15-25% without compromising service quality. Center of excellence development serves as an effective differentiation strategy for attracting non-JKN patient segments. Optimal BOR management (>75%) and LOS control aligned with INA-CBGs standards are key to hospital financial sustainability. These findings underscore the need for a comprehensive strategic approach that integrates operational efficiency with enhanced patient service value.